Evaluation of solar photovoltaic panel performance and estimation of solar energy potential in Kota Kinabalu, Sabah - Kartini Sukarno (2017)
The world is currently facing environmental damages partially caused by increasing in energy consumption from conventional energy sources such as fossil fuels. Hence, renewable energy such as solar energy, which is regenerated naturally, is currently receiving considerable attention for energy generation. To sustain electricity generation from solar energy, consistent solar radiation is preferable throughout the year, and complete information on the daily, monthly and yearly radiation profile are required for further development planning. Kota Kinabalu, the capital city located in the west coast of Sabah, was claimed to be one of the areas that receives the highest solar radiation every year in Malaysia. This research was carried out to assess the potential of electricity generation in Kota Kinabalu that may serves as guidelines for future planning. The global solar radiation was first measured and acquired for the year 2014 and 2015 in Kota Kinabalu. Concurrently, electrical power generation was assessed using solar photovoltaic panels at certain period of time. From these data, prediction was carried out to assess the potential electrical generation in Kota Kinabalu for that years. It was found that total energy received in 2014 was 1.6MWh/m2 with the average of 133.4kWh/m2 and the maximum peak of the global solar radiation was 1065.4W/m2 on 2nd November 2014. On the other hand, the total global solar radiation received in 2015 was 2.1MWh/m2 with the average of 175kWh/m2 and the maximum peak was 1086.98W/m2 on 12th March 2015. For electrical energy generation, it was found that the actual efficiency of energy conversion for uncooled and fixed solar photovoltaic panel was 13%. As a comparison, continuous cooling of the fixed solar panel had increased the efficiency to up to 16.7% whereas for uncooled dual tracking solar panel, the efficiency was slightly low which is 15.1%. With this efficiency, over 200kWh/m2 of electricity could have been generated in each year in 2014 and 2015 using uncooled and fixed solar photovoltaic panel. On the other hand, almost 300kWh/m2 could have been generated in 2014 and over 300 kWh/m2 in 2015 when the solar panel was fixed but continuously cooled. However, just over 200kWh/m2 and 300kWh/m2 could have been generated in 2014 and 2015, respectively, when the solar panel has dual axis sun tracking system, without incorporating the cooling system. These amounts of electricity are quite substantial which shows the potential for developing solar energy power in Kota Kinabalu.